Sequences, Series, Sigma Notation and Binomial Theorem

Types of Sequences 1. Arithmetic Progression: a, a + d, a + 2d, … , a + (n-1)d, … 2. Geometric Progression: a, ar, ar2, … , arn-1, … 3. Others: u1, u2, u3, … , un, … in general. Notation Notation a d r Tn or un Sn Meaning First term of a sequence, particularly in an AP or GP. Common difference of an AP. Common ratio of a GP. nth term of sequence. Sum of the first n terms of a series. This notation is used particularly in the context of AP and GP before the introduction of the sigma notation. The series in context need not necessarily be an AP or GP.

Formulae Description nth term Sum of the first n terms AP Tn = a + (n − 1)d
Sn = n (2a + ( n − 1)d ) 2

GP
Tn = ar
n −1

a(1 − r n ) is applicable for all 1− r values of r ≠ 1 Sn =

Sum to infinity

n (a + Tn ) where 2 Tn = a + (n − 1)d is the last term or nth term. Sn =

Common difference/ratio Mean

d = Tn − Tn −1

a which exists provided 1− r −1 < r < 1 r = Tn ÷ Tn −1 Sn =

Description Sum of the first n terms

Arithmetic mean of x and y is Geometric mean of x and y is x+ y ± xy . . 2 Sequences in general (AP, GP or otherwise). Using the notation Sn and Tn Using the sigma notation n S n = T1 + T2 + T3 + … + Tn ∑ u r = u1 + u 2 + u3 + … + u n
r =1

http://education.helixated.com An Open Source Education Project

1

nth term First term Sum from the (m+1)th term to the nth term

Tn = S n − S n −1

un = ∑ ur − ∑ ur
r =1 1 r =1

n

n −1

T1 = S1
S n − S m = Tm +1 + Tm + 2 + … + Tn

u1 = ∑ u r
r =1

∑u − ∑u
r =1 r r =1

n

m

r

= u m +1 + u m + 2 + … + u n

Example 1: A geometric series has first term 1 and common ratio 2. Find the least value of n for which the sum of the first n terms exceeds the value 1000. Example 2: The sum of the first 50 terms of an arithmetic series is twice that of the sum of the terms from the 26th to the 50th inclusive. Find the common difference of this series in terms of a where a is the first term. Find the minimum number of terms required for the sum to exceed 1300a. Some Other Properties of Sigma Notation 1. 2. 3.

∑ (a r + br ) = ∑ a r + ∑ br .

n

n

n

∑ ka
r =1

r =1 n

r =1

r =1

r

= k ∑ a r where k is a constant.
r =1

n

⎛ n ⎞⎛ n ⎞ a r br ≠ ⎜ ∑ a r ⎟⎜ ∑ br ⎟ in general. ∑ r =1 ⎝ r =1 ⎠⎝ r =1 ⎠
n

Some Standard Results 1. 2.

∑ r = 2 n(n + 1) (You are expected to know this result because it is an AP)

n

1

1 n(n + 1)(2n + 1) 6 r =1 n 1 3. ∑ r 3 = n 2 (n + 1) 2 4 r =1

∑r

r =1 n

2

=

Remarks: Results for (2) and (3) will be given to you in the question if it is needed. Example 3: Express that

r = n +1

∑ r (r + 1) in terms of n given that

2n

∑r
r =1

n

2

=

1 n(n + 1)(2n + 1) . 6

http://education.helixated.com An Open Source Education Project

2

Method of Differences If a r , the general term of a sigma notation
f ( r + 1) − f ( r ) , then we have

∑a
r =1

n

r

, can be expressed in the form

∑ [ f (r + 1) − f (r )]
r =1

n

= ∑ f ( r + 1) − ∑ f ( r )
= [ f (2) + f (3) + f (4) + … f (n) + f (n + 1)] − [ f (1) + f (2) + f (3) + f (4) +
= f ( n + 1) − f (1)
r =1 r =1

n

n

+ f ( n)]

Example 4: Express

1 A B in the form . Hence, or otherwise, find + (r + 1)(r + 2) r +1 r + 2 n ∞ 1 1 ∑ (r + 1)(r + 2) in terms of n and deduce the value of ∑ (r + 1)(r + 2) . r =1 r =1

Binomial Theorem There are 2 formulae with 2 different conditions and applications. 1. ⎛n⎞ ⎛n⎞ ⎛n⎞ ⎛ n ⎞ n −1 n = x n + ⎜ ⎟ x n −1 y + ⎜ ⎟ x n − 2 y 2 + … + ⎜ ⎟ x n − r y r + … + ⎜ ⎜1⎟ ⎜ 2⎟ ⎜r⎟ ⎜ n − 1⎟ xy + y ⎟ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠ n(n − 1) 2 n(n − 1)(n − 2) 3 n(n − 1)(n − 2)… (n − r + 1) r n 2. (1 + x ) = 1 + nx + x + x +… + x +… 2! 3! r! where x < 1 (i.e. − 1 < x < 1 )

( x + y )n

The first formula is used to expand the sum of 2 terms taken to the power of a positive integer n. Without this formula, it is still possible to expand ( x + y ) n slowly, step by step, although it would be silly to do so. The second formula gives us an infinite series. The term (1 + x) n has a power n which can take values that are both positive and negative. Unlike the first formula where the power n is only restricted to positive integer, the power n in the second formula can be a 1 3 fraction such as or − . This is definitely a much more powerful formula but the 2 2 condition for the application of the formula is much more stringent. One of the 2 terms in the bracket has to be a 1 and the range of the other term x in the bracket has to be in the range from − 1 to 1 (i.e. − 1 < x < 1 ).
http://education.helixated.com An Open Source Education Project

3

Example 5: Use the binomial theorem to find the first four non-zero terms of the series expansion of ( 4 + 3 x ) 2 in (a) ascending powers of x, (b) descending powers of x, giving the range of x in each case. We can use the infinite geometric series 1 + r + r 2 + … + r n + … = expand (1 + x ) −1 easily simply by equating r = − x . Example 6: Use the binomial theorem to find the first four non-zero terms of the series expansion of (4 + x) −1 in (a) ascending powers of x and (b) descending powers of x, giving the range of x in each case. Using Partial Fraction in conjunction with Binomial Theorem Example 7: Let f ( x) = 4x 2 + 2x + 6 A Bx + C . Express in the form and find + 2 2 + x 1 + 2x 2 (2 + x)(1 + 2 x )
1 = (1 − r ) −1 to 1− r
1

the series expansion of f(x) in ascending powers of x up to and including the terms in x 4 . Find the coefficient of x 2 n in terms of n.

http://education.helixated.com An Open Source Education Project

4

Sign up to vote on this title
UsefulNot useful